ANALYSIS OF PERCEIVED RISK AND PERCEIVED BENEFIT INFLUENCING ONLINE SHOPPING BEHAVIOR IN MANADO - Bangkit, Josefine L. K.; Tumbuan, Willem J. F. A.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2022)
Understanding the behavior of consumersâ€™ online shopping, especially factors that influence the online shopping is considered important for marketers in order to increase the volume of online shopping. In this research, the researcher focused on people who had experience on online shopping in Manado, so the researcher conducted research on variables that influencing online shopping behavior, in this case the variables are perceived risk and perceived benefit. The purpose of this study is to analyze perceived risk and perceived benefit influencing online shopping behavior in Manado. The quantitative method is used in this research. In order to collect data, questionnaires were distributed to 100 respondents in Manado. The result of this research shows that perceived risk and perceived benefit has significant influence on online shopping behavior.Â Keywords: online shopping behavior, perceived risk, perceived benefit